USING MAXENT TO ASSESS THE IMPACT OF CLIMATE CHANGE ON THE DISTRIBUTION OF SOUTHERN YELLOW-CHEEKED CRESTED GIBBON (Nomascus gabriellae) - Tien Thinh, Vu; Van Dung, Tran; Quang Vinh, Luu; Tuyet Nga, Ta (Journal of Forestry Science and Technology, 2018)
Climate change has a variety of impacts that might have negative impacts on wildlife species, especially their distribution. Species with narrow distributions are are more sensitive than the other species. In this study, we used ecological niche modelling species (MaxEnt software), species occurrence data, and environmental variables to assess the impacts of climate change on the distribution of Southern yellow-cheeked crested gibbon (Nomascus gabriellae) - an endemic and rare primate species of Vietnam and Cambodia with narrow distribution range. We used environmental variables to generate the potential distribution of Southern Yellow-cheeked Crested Gibbon at current and two times in future (2050 and 2070). In addition, two scenarios of climate change (RCP4.5 and RCP8.5) and three climate models (ACCESS1 - 0; GFDL - CM3; MPI - ESM - LR) were used to evaluate the changed of suitable distribution in the future. The results show that the distribution of this species was predicted to decrease dramatically under the effects of climate change. Futhermore, the projections indicate that a larger suitable area will disappear. The suitable areas are likely to shift toward the center of current distribution range and areas with high elevation above sea level. In addition, we assessed the priority of protected areas in gibbon conservation under climate change context.